Rapid identification of pathogens in blood serum via Raman tweezers in combination with advanced processing methods - Vaculík, Ondřej; Bernatová, Silvie; Rebrošová, Katarína; Samek, Ota; Šilhan, Lukáš; Růžička, Filip; Šerý, Mojmír; Šiler, Martin; Ježek, Jan; Zemánek, Pavel (Biomedical optics express, 2023)
Pathogenic microbes contribute to several major global diseases that kill millions of people every year. Bloodstream infections caused by these microbes are associated with high morbidity and mortality rates, which are among the most common causes of hospitalizations. The search for the "Holy Grail" in clinical diagnostic microbiology, a reliable, accurate, low cost, real-time, and easy-to-use diagnostic method, is one of the essential issues in clinical practice. These very critical conditions can be met by Raman tweezers in combination with advanced analysis methods. Here, we present a proof-of-concept study based on Raman tweezers combined with spectral mixture analysis that allows for the identification of microbial strains directly from human blood serum without user intervention, thus eliminating the influence of a data analyst.